pengaruh Pengaruh Budaya Organisasi Dan Komunikasi Organisasi Terhadap Kinerja Guru Di SD Negeri 11 Kecamatan Rantau Utara Kabupaten Labuhan Batu - Rizki, Vitri Dea; Safina, Wan Dian; Hidayat, Toni; Rukmini, Rukmini (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
It turns out that organizational culture has a strong influence on teacher performance, while organizational communication has a weaker influence on teacher performance. This was revealed from the results of research conducted on 33 elementary school teachers at SD Negeri 11, Rantau Utara District, Labuhan Batu Regency. The results of multiple regression analysis via SPSS 24 output show the linear regression equation Y= 0.091+0.828X1+0.360X2 meaning that if there is an effort to increase 1 (one) unit then teacher performance will increase by 0.828, likewise organizational communication will increase teacher performance by 0.360. Next, the hypothesis using the t-test via SPSS 24 output shows that tsig 0.000 < 0.1, which means Ha is accepted. Likewise, the F-test shows that Fsig 0.000 < 0.1. Considering that organizational communication has a smaller influence than organizational culture, it is recommended to strengthen organizational communication in elementary schools, through the provision of bookshelves displaying educational magazines such as educational nimbar, educational selecta, testing magazines, etc. To be a reference for teachers.